User characteristics and performance with automated mobile phone systems. (14th January 2008) - Howell, Mark; Love, Steve; Turner, Mark
The aim of this study was to investigate the impact of individual differences (such as gender and attitude towards mobile phone use in public places) on the usability of a speech-activated mobile city guide service in various context of use (e.g. cafe, train). A Wizard of Oz methodology was used to provide the service functionality for the mobile city guide service. Participants in the study completed specific tasks over a six-week period in public and private locations. The results highlight the importance of considering the effects of individual differences on the context of use in system design and evaluation.